2019
DOI: 10.3847/2041-8213/ab4bcd
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered Kelvin–Helmholtz Instability in the Solar Corona

Abstract: The Kelvin-Helmholtz (KH) instability is commonly found in many astrophysical, laboratory, and space plasmas. It could mix plasma components of different properties and convert dynamic fluid energy from large scale structure to smaller ones. In this study, we combined the ground-based New Vacuum Solar Telescope (NVST) and the Solar Dynamic Observatories (SDO) / Atmospheric Imaging Assembly (AIA) to observe the plasma dynamics associated with active region 12673 on 09 September 2017. In this multi-temperature v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…(iii) Kelvin-Helmholtz instability KH instability is a basic physical process that occurs when there is velocity shear in a single continuous fluid, or when there is a velocity difference across the interface between two fluids [147]. Recent observations have revealed the occurrence of KH instability in the solar atmosphere, such as at the interface between an erupting region and the surrounding corona [148], at the outer edge of CMEs [149], in prominences [150], in coronal streamers [151] and in solar jets [152,153].…”
Section: (Ii) Plasmoidmentioning
confidence: 99%
See 2 more Smart Citations
“…(iii) Kelvin-Helmholtz instability KH instability is a basic physical process that occurs when there is velocity shear in a single continuous fluid, or when there is a velocity difference across the interface between two fluids [147]. Recent observations have revealed the occurrence of KH instability in the solar atmosphere, such as at the interface between an erupting region and the surrounding corona [148], at the outer edge of CMEs [149], in prominences [150], in coronal streamers [151] and in solar jets [152,153].…”
Section: (Ii) Plasmoidmentioning
confidence: 99%
“…Using IRIS observations, Li et al [152] reported the developing process of KH instability in a blowout jet due to the strong velocity shear of two plasma flows along the jet spire, in which the developing process was about 80 s and the distortion scale was less than 1.6 Mm. Using H α observations taken by the NVST, Yuan et al [153] studied the KH instability at the outer edge of a small solar jet, in which the KH instability was thought to be caused by the shearing motion between cool chromospheric and hot coronal plasma flows. During the mature stage, plasma heating was evidenced around the region of the vortex structures, supporting the scenario that KH instability can effectively transfer plasma kinetic energy into thermal energy and heat the coronal plasma.…”
Section: Observational Featurementioning
confidence: 99%
See 1 more Smart Citation
“…However, observations of the KHI have been scarce so far, either limited to quiescent prominences (e.g. Berger et al, 2010, see also Section 4.9.3) or to very energetic events, such as CME eruptions (Foullon et al, 2011) or flares (Brannon, Longcope, and Qiu, 2015;Yuan et al, 2019). Observations of the KHI in quiescent prominences with IRIS suggest that only large field-aligned shear flows (with Alfvén Mach number larger than 2) are able to trigger the instability in such conditions (Hillier and Polito, 2018, see also Figure 18 and Section 4.9.3).…”
Section: Fundamental Mhd Instabilitiesmentioning
confidence: 99%
“…The slow solar wind that emerges from the equatorial region of the Sun is considered to be affected by the turbulent shear source (see Adhikari et al 2020b). Kelvin-Helmholtz instabilities may develop in the inner and outer corona (DeForest et al 2016;Yuan et al 2019), which may provide a source of turbulence shear source close to the Sun (Ruffolo et al 2020) and may affect the slow and fast solar wind from above the sonic point. We will address this issue in a future paper.…”
Section: Solar Wind Plus Ni Mhd Turbulence Transport Modelmentioning
confidence: 99%